Learning Assessment Model for Islamic Religious Education - Rani Putri Prihatin; Tasman Hamami (Nusantara: Jurnal Pendidikan Indonesia, 2022)
Assessment is not only seen as giving value through a series of tests, but also must be an integral part of learning. This paper tries to explain the development of an assessment model that can be used by teachers as a measuring tool after the learning unit is completed. This is also supported by several studies which reveal that assessment can improve learning. In this case, the assessment model is summarized into assessment for learning, assessment of learning, assessment as learning, and authentic assessment. This research uses a literature study approach with qualitative methods. The data obtained were obtained from the search results of various works of literature, namely books and relevant journals. After collecting the data, then analyzing the data results and focusing on the problem points. In addition, in every writing, every reference is always checked. This study describes authentic assessment in learning. The results of the assessment of Islamic religious education learning have emphasized what part must be assessed, namely the demand for competence in Islamic teachings that can be applied in everyday life. We can see this in the dominant aspects such as attitudes, skills, and knowledge, based on these aspects the teacher can collect student data using authentic assessment where student learning outcomes are shown based on achievement and learning outcomes in the form of abilities in real life.